On the Priesthood: Classic and Contemporary Texts - Levering, Matthew (Rowman & Littlefield Publishers, 2003)
Controversy about the Catholic priesthood is nothing new. Just like laity, priests (including bishops and popes) have always been sinners. Some priests, like some laity, have caused grave scandal throughout the 2000-year history of the Church. Two questions arise from this reality. Why did Jesus Christ establish a ministerial priesthood for his Church, if the priesthood would sometimes cause scandal—what did he intend for the priesthood? Second, what has the Catholic Church in past times done about scandal in the priesthood—how has the Church corrected its priests and encouraged priests to lead lives of holiness? Amidst the noisy din of talking heads and self-proclaimed experts, this book offers solid warnings and directions about the priesthood from 15 saints of the past two millennia. On the Priesthood serves as a readable guide for priests, seminarians, and educated readers seeking to learn more about the simultaneous unworthiness and dignity of the priesthood. Always challenging and penetrating, the selections unite around one key point; the need for holiness.